2020
DOI: 10.1016/j.omtm.2019.11.017
|View full text |Cite
|
Sign up to set email alerts
|

C3 Transferase-Expressing scAAV2 Transduces Ocular Anterior Segment Tissues and Lowers Intraocular Pressure in Mouse and Monkey

Abstract: Glaucoma is a lifelong disease with elevated intraocular pressure (IOP) as the main risk factor, and reduction of IOP remains the major treatment for this disease. However, current IOP-lowering therapies are far from being satisfactory. We have demonstrated that the lentivirus-mediated exoenzyme C3 transferase (C3) expression in rat and monkey eyes induced relatively long-term IOP reduction. We now show that intracameral injection of self-complementary AAV2 containing a C3 gene into mouse and monkey eyes resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 59 publications
3
26
0
Order By: Relevance
“…5,40 Furthermore, as long as the serotype of AAV is considered, our previous studies demonstrated that intracameral injection of scAAV2-C3 induced a longterm IOP-lowering effect in monkey eyes. 41 Bogner et al 42 suggested that scAAV2-based vectors transduced the TM of mice and rats more effectively than did scAAV8-based vectors. In addition, the scAAV2 vector transduces RGCs around the optic nerve head more efficiently than do scAAV5 and scAAV8 after intravitreal injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,40 Furthermore, as long as the serotype of AAV is considered, our previous studies demonstrated that intracameral injection of scAAV2-C3 induced a longterm IOP-lowering effect in monkey eyes. 41 Bogner et al 42 suggested that scAAV2-based vectors transduced the TM of mice and rats more effectively than did scAAV8-based vectors. In addition, the scAAV2 vector transduces RGCs around the optic nerve head more efficiently than do scAAV5 and scAAV8 after intravitreal injection.…”
Section: Discussionmentioning
confidence: 99%
“…Vector Construction scAAV2-EGFP (1 Â 10 12 viral genomes [vg]/mL) and scAAV2-C3 (5 Â 10 11 vg/mL) vectors were prepared by the Beijing FivePlus Molecular Medicine Institute (FMMI) (Beijing, China), as previously described. 41…”
Section: Methodsmentioning
confidence: 99%
“…In addition, RhoA induced ECM accumulation and activated myofibroblast-like cells. These findings indicated that DEX may induce the fibrotic activity in HTM cells through the RhoA/ROCK pathway and that RhoA probably serves as an intervening factor for lowering IOP ( Rao et al, 2017 ; Tan et al, 2018 ; Tan et al, 2019 ; Chen et al, 2020 ; Tan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 88%
“…RhoAG14V, a constitutively active variant of RhoA, has been reported to induce ECM synthesis ( Pattabiraman and Rao, 2010 ) and decrease AH outflow through the TM in anterior chambers ( Pattabiraman et al, 2015 ). Other studies have suggested that the RhoA/ROCK plays an important role in regulating IOP, which was reduced in the presence of RhoA inhibitor C3 transferase ( Tan et al, 2018 ; Tan et al, 2019 ; Tan et al, 2020 ) and ROCK inhibitor Y-27632 ( Pattabiraman et al, 2015 ; Chen et al, 2020 ). Based on these findings, it was demonstrated that DEX not only increased the expression level of RhoA but also activated ROCK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation